Identifikasi Bakteri Asam Laktat pada Fermentasi Symbiotic Culture of Bacteria and Yeast (Scoby) dengan Teh Putih dan Gula Merah - Barrianti Barrianti; Cep Wahyu; Bunga Salma Fitriani (Syntax Corporation, 2023)
A decreased immune system can cause diseases of the digestive tract such as diarrhea. Treatment of diarrhea with antibiotics which causes many negative impacts from antibiotic resistance has made people turn to the use of probiotics as an alternative treatment. Several studies have stated that the probiotic bacteria found in probiotic kombucha drinks, such as lactic acid bacteria, can be useful for maintaining the balance of the digestive tract microflora by helping inhibit the growth of pathogenic bacteria that cause diarrhea. The aim of this study is to identify the species of lactic acid bacteria that play a role in probiotic kombucha drinks. This study uses a descriptive experimental design, namely describing the results of study data in the form of pictures and tables and then drawing conclusions. The results obtained from the study that has been carried out are yeast microorganisms with the species Saccharomyces cerevisiae, Candida spherica, Candida lambica, Candida inconspicua, and Candida krusei. Meanwhile, bacteria suspected to be lactic acid bacteria of the genus Lactobacillus could not be identified by the vitek tool. In this study it can be concluded that no species of lactic acid bacteria could be found in all isolates obtained from samples of probiotic kombucha drinks made from white tea and brown sugar.